Diversity and Functional Insights into Endophytic Fungi in Halophytes from West Ordos Desert Ecosystems - Xingzhe Wang; Yan Zhang; Jingpeng Li; Yiteng Ding; Xiaodan Ma; Peng Zhang; Haijing Liu; Jie Wei; Yuying Bao (Journal of Fungi)
Arid desert regions are among the harshest ecological environments on Earth. Halophytes, with their unique physiological characteristics and adaptability, have become the dominant vegetation in these areas. Currently, research on halophytes in this region is relatively limited, particularly concerning studies related to their root endophytic fungi, which have been rarely reported on. Therefore, investigating the diversity and composition of endophytic fungi in halophytes is crucial for maintaining ecological balance in such an arid environment. This study focuses on eight representative angiosperm halophytes from the West Ordos Desert in China (including Nitraria tangutorum, Salsola passerina, Suaeda glauca, Reaumuria trigyna, Reaumuria kaschgarica, Limonium aureum, Apocynum venetum, and Tripolium vulgare), utilizing Illumina MiSeq high-throughput sequencing technology combined with soil physicochemical factor data to analyze the diversity, composition, and ecological functions of their root-associated fungal communities. Ascomycota dominated the fungal composition in most halophytes, particularly among the recretohalophytes, where it accounted for an average of 88.45%, while Basidiomycota was predominant in Suaeda glauca. A Circos analysis of the top 10 most abundant genera revealed Fusarium, Dipodascus, Curvularia, Penicillium, and other dominant genera. Co-occurrence network analysis showed significant differences in fungal networks across halophyte types, with the most complex network observed in excreting halophytes, characterized by the highest number of nodes and connections, indicating tighter fungal symbiotic relationships. In contrast, fungal networks in pseudohalophytes were relatively simple, reflecting lower community cohesiveness. Redundancy analysis (RDA) and Mantel tests demonstrated that soil factors such as organic matter, available sulfur, and urease significantly influenced fungal diversity, richness, and evenness, suggesting that soil physicochemical properties play a critical role in regulating fungal–plant symbiosis. Functional predictions indicated that endophytic fungi play important roles in metabolic pathways such as nucleotide biosynthesis, carbohydrate degradation, and lipid metabolism, which may enhance plant survival in saline–alkaline and arid environments. Furthermore, the high abundance of plant pathogens and saprotrophs in some fungal communities suggests their potential roles in plant defense and organic matter decomposition. The results of this study provide a reference for advancing the development and utilization of halophyte endophytic fungal resources, with applications in desert ecosystem restoration and halophyte cultivation.